2019
DOI: 10.1136/jnnp-2019-321794
|View full text |Cite
|
Sign up to set email alerts
|

Risk of spread in adult-onset isolated focal dystonia: a prospective international cohort study

Abstract: ObjectiveIsolated focal dystonia can spread to muscles beyond the initially affected body region, but risk of spread has not been evaluated in a prospective manner. Furthermore, body regions at risk for spread and the clinical factors associated with spread risk are not well characterised. We sought here to prospectively characterise risk of spread in recently diagnosed adult-onset isolated focal dystonia patients.MethodsPatients enrolled in the Dystonia Coalition with isolated dystonia affecting only the neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
68
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 24 publications
14
68
5
1
Order By: Relevance
“…The late age of onset and the relatively high tendency to spread of non-task-specific ULD are clinical features similar to those also reported in blepharospasm and differ from those reported in cervical dystonia and task-specific ULD. 10,16 The presence of dystonic tremor in non-task-specific and task-specific ULD supports the observation that tremor is a phenotypic feature of dystonia. 17 Although we did not have data on the time of appearance of tremor and dystonia, the higher frequency of tremor among non-task-specific patients may reflect the greater frequency of segmental dystonia in this group, supporting previous reports that suggest that dystonia spreads more commonly in patients with tremor.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The late age of onset and the relatively high tendency to spread of non-task-specific ULD are clinical features similar to those also reported in blepharospasm and differ from those reported in cervical dystonia and task-specific ULD. 10,16 The presence of dystonic tremor in non-task-specific and task-specific ULD supports the observation that tremor is a phenotypic feature of dystonia. 17 Although we did not have data on the time of appearance of tremor and dystonia, the higher frequency of tremor among non-task-specific patients may reflect the greater frequency of segmental dystonia in this group, supporting previous reports that suggest that dystonia spreads more commonly in patients with tremor.…”
Section: Discussionsupporting
confidence: 69%
“…Likewise, there is no relationship between age of onset and tremor frequency 17,18 or between age of onset and tendency to spread in patients with different focal adult-onset dystonias. 10,16 The findings of the present study also introduce the possibility that non-taskspecific and task-specific ULD are distinct clinical subtypes. In a previous article, we reported that patients with different forms of focal adult-onset dystonia show differences in several clinical, demographic, and neurophysiological features.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…13,[15][16][17][18][19][20] In fact, prospective analysis in a relatively small adult-onset component of the current data set demonstrated a relationship between initial body region affected (including hand) and risk of spread. 21 Thus, clinical and demographic features are critical for understanding important subtypes of ULD. Such clinical characteristics are essential for design and implementation of future studies that aim to test symptomatic or disease-modifying interventions in isolated limb dystonia.…”
mentioning
confidence: 99%
“…Such clinical characteristics are essential for design and implementation of future studies that aim to test symptomatic or disease-modifying interventions in isolated limb dystonia. 21,22 The primary aim of this report is to characterize clinical features and demographics of isolated ULD where the upper limb was involved at onset. Data are derived from the Dystonia Coalition database, the largest standardized, multicenter cohort ever assembled.…”
mentioning
confidence: 99%